1508 Is hospital sanitation personnel exposed to antineoplastic agents?. (24th April 2018) - Labrèche, F; Roberge, B; Yennek, A; Caron, NJ; Bussières, J-F
Abstract : Introduction: Exposure to antineoplastic drugs (ANPs) occurs mainly through dermal contact. In hospital settings, pharmacy and nursing personnel are considered the most exposed workers and receive training on handling dangerous drugs. There is, however, little data on exposure of hospital sanitation (HS) personnel. Our main objective is to document the potential exposure of HS personnel by exploring surface contamination. Methods: Following a preliminary visit to identify target surfaces, 75 wipe samples were taken on surfaces often touched by the HS personnel and 21 samples on other hi-touch surfaces, in three oncology departments: pharmacy, outpatient clinic and hospital ward. Sampled areas varied from 160–1700 cm 2 . A few hand wipe samples were also collected to explore skin contamination. Wipes were analysed by ultra-performance liquid chromatography tandem-mass spectrometry for 10 ANPs. Limits of detection (LOD) varied by a factor of 10 according to sampled area and ANP. Descriptive statistics are presented here. Result: Overall, 11 of the 16 types (68.8%) of sampled surfaces were above the LOD for at least one ANP; gemcitabine and cyclophosphamide were most often identified (30.6% and 29.8% of samples respectively), followed by 5-fluorouracil and irinotecan (both 15.6% above LOD). Highest levels were all found in the outpatient clinic: 5-fluorouracil (49 ng/cm 2 ) and irinotecan (3.6 ng/cm 2 ), toilet floor; cyclophosphamide (19.6 ng/cm 2 ), IV pump; gemcitabine (4.97 ng/cm 2 ), cytotoxic waste bin cover. Hand wipes were above the LOD for five of seven nurses, one of seven pharmacy personnel and none of three sampled HS workers. Discussion: A notable proportion of surfaces showed measurable levels of ANPs, with highest concentrations on surfaces cleaned by HS personnel. Prevention programs should integrate regular monitoring of hospital surfaces in order to evaluate environmental contamination and sharing monitoring results with all concerned personnel, together with appropriate training, in order to raise their awareness of ANP exposures.